2019
DOI: 10.1080/09506608.2019.1694779
|View full text |Cite
|
Sign up to set email alerts
|

Model-driven design of bioactive glasses: from molecular dynamics through machine learning

Abstract: Research in bioactive glasses (BGs) has traditionally been performed through trial-and-error experimentation. However, several modelling techniques will accelerate the discovery of new BGs as part of the ongoing endeavour to 'decode the glass genome.' Here, we critically review recent publications applying molecular dynamics simulations, machine learning approaches, and other modelling techniques for understanding BGs. We argue that modelling should be utilised more frequently in the design of BGs to achieve p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 212 publications
0
28
0
Order By: Relevance
“…Looking at the future, further improvements in the predictive capability could be achieved by applying molecular dynamics simulations and machine learning approaches, which are already implemented for the design of bioactive glasses to tailor specific properties, such as density, dissolution kinetics and bioactivity, or model the biological response, such as the glass ability to foster protein adsorption, cell adhesion, cell proliferation and antibacterial effects [37,38]. Indeed, a critical issue to be considered concerns the incorporation of scaffold microstructure in the simulation and modelling procedures, carrying the risk to further increase the algorithmic complexity and computational cost.…”
Section: Resultsmentioning
confidence: 99%
“…Looking at the future, further improvements in the predictive capability could be achieved by applying molecular dynamics simulations and machine learning approaches, which are already implemented for the design of bioactive glasses to tailor specific properties, such as density, dissolution kinetics and bioactivity, or model the biological response, such as the glass ability to foster protein adsorption, cell adhesion, cell proliferation and antibacterial effects [37,38]. Indeed, a critical issue to be considered concerns the incorporation of scaffold microstructure in the simulation and modelling procedures, carrying the risk to further increase the algorithmic complexity and computational cost.…”
Section: Resultsmentioning
confidence: 99%
“…Preceramic polycarbosilane polymers are commonly used as precursors to make ceramic fibers 10,39 and ceramic matrix. [7][8][9]40,41 The chemical and volume changes that accompany ceramization of the polymer during pyrolysis have been documented in several studies. For example, see Refs [39][40][41][42].…”
Section: Santhosh Et Almentioning
confidence: 99%
“…Some of the areas where reinforcement learning can have applications include the design of smart robots (robotics), which allow automated high‐throughput synthesis, characterization, selection, and design of novel materials 30 . A review of some of the algorithms used in materials science and glass science can be found elsewhere 15,34‐36 …”
Section: Artificial Intelligence and Machine Learningmentioning
confidence: 99%
“…30 A review of some of the algorithms used in materials science and glass science can be found elsewhere. 15,[34][35][36]…”
mentioning
confidence: 99%